Respuesta :

Answer:

First choice is the right answer (-∞, -9] or (2, ∞)

Step-by-step explanation:

I. Solve 1st problem 2(2x - 1)  > 6

                 4x-2 > 6

                 4x > 6+2

                  x > 2

II. Solve 2nd problem x + 3 <=  -6

                 x <= -6-3

                 x <= -9

III. Prove the answer

         if x > 2 then x = 3

          2( 2(3)-1 ) > 6

          2(5) > 6

           10 > 6  so the answer is true

     

         if x <= -9 then x = -9

           -9 + 3 <= -6

                  -6 <= -6 so the answer is true

Hope that help :D